En busca de Catalina de Erauso identidades en conflicto en la vida de la monja alférez - Mendieta, Eva. (Castelló de la Plana : Publicaciones de la Universitat Jaume I, Servei de Comunicació y Publicacions, 2010)
An investigation of the life and historical milieu of Catalina de Erauso (1592-1650), the lieutenant nun, with emphasis on her national and gender identities.
Includes bibliographical references (p. [287]-300) and index.
Keywords: Erauso, Catalina de, -- b. ca. 1592.; Spain -- Biography; Latin America -- Biography; Soldiers -- Latin America -- Biography; Women soldiers -- Latin America -- Biography; Basques -- Latin America -- Biography; New Spain -- History -- 17th century; National characteristics -- Case studies; Gender identity -- Case studies; Nuns -- Spain -- País Vasco -- Biography; Electronic books